2018
DOI: 10.1111/bph.14460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non‐euphoric plant cannabinoids on muscle quality and performance of dystrophic mdx mice

Abstract: We provide new insights into plant cannabinoid interactions with TRP channels in skeletal muscle, highlighting a potential opportunity for novel co-adjuvant therapies to prevent muscle degeneration in DMD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 67 publications
1
62
0
Order By: Relevance
“…In addition to histological and functional protection in the dystrophin‐deficient soleus, PGC‐1α overexpression also altered gene expression suggestive of increased autophagy in the same animals used herein (Hollinger et al, ). In studies using limb muscle of approximately the same age, dystrophin deficiency has been shown to increase LC3I protein abundance while effects on LC3II are equivocal (Fiacco et al, ; Iannotti et al, ). In the present investigation evaluating the gastrocnemius, our data suggest increased autophagosome formation following PGC‐1α overexpression (increased LC3II) and increased degradation (similar p62).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to histological and functional protection in the dystrophin‐deficient soleus, PGC‐1α overexpression also altered gene expression suggestive of increased autophagy in the same animals used herein (Hollinger et al, ). In studies using limb muscle of approximately the same age, dystrophin deficiency has been shown to increase LC3I protein abundance while effects on LC3II are equivocal (Fiacco et al, ; Iannotti et al, ). In the present investigation evaluating the gastrocnemius, our data suggest increased autophagosome formation following PGC‐1α overexpression (increased LC3II) and increased degradation (similar p62).…”
Section: Discussionmentioning
confidence: 99%
“…on transcription and synthesis of pro-inflammatory markers (i.e. IL-6 receptors, TNF-α, TNF-β1, and inducible nitric oxide synthase) in the gastrocnemius and diaphragm of dystrophic MDX mice (a mouse model of Duchenne muscular dystrophy) [91]. In this investigation, CBD attenuated mRNA expression of each marker and reduced plasma concentrations of IL-6 and TNFα.…”
Section: Exercise-induced Muscle Damage-muscle Function Soreness Anmentioning
confidence: 66%
“…CBD may be useful for treating bladder dysfunction [112]. It is also reported that CBD), cannabidivarin (CBDV) and tetrahydrocannabidivarin (THCV), can reduce inflammation and restore functional autophagy and positively enhance muscle function in vivo [113].…”
Section: Medicalmentioning
confidence: 99%